An approach for aggregation and historicization of production entities in the graph - Schmied, Sebastian; Grosmann, Daniel; Mathias, Selvine G.; Klaus Mueller, Ralph (Proceedings (IEEE International Conference on Emerging Technologies and Factory Automation), 2020)
A production system consists of multiple production entities. To enable a manufacturing process, these entities have to exchange information. Information models offer the possibility to standardize the data exchange between the entities. In addition to a common communication protocol, concepts that integrate and aggregate the different entities into a common address space, have to be developed. Another important issue is the historicization of information, for example, to improve the production process or for legal reasons. Graph databases enable semantic relations between objects for representation and storage of information. Therefore, it is a promising concept to be used in the production context. This paper presents a concept for the aggregation and historicization of production entities into a graph database.